2020
DOI: 10.1016/j.accpm.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation changes and thromboembolic risk in COVID-19 obstetric patients

Abstract: Elsevier Masson SAS on behalf of Socié té française d'anesthé sie et de ré animation (Sfar).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 22 publications
2
67
0
12
Order By: Relevance
“…SARS-CoV-2 has an impact on coagulation, yet coagulation is already altered by pregnancy itself [ 25 ]. Whether SARS-CoV-2 can be attributable to the vascular and circulatory pathologies still needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 has an impact on coagulation, yet coagulation is already altered by pregnancy itself [ 25 ]. Whether SARS-CoV-2 can be attributable to the vascular and circulatory pathologies still needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, while reviews and case reports in nonpregnant populations have reported some severe morbidity and even mortality in COVID-19 associated with bleeding or hemorrhage, [1][2][3][4] there have been very limited data regarding specific laboratory derangements that may be predictive for or associated with bleeding risk related to COVID-19. [16][17][18] Further research should continue to investigate the impact of a COVID-19 diagnosis on hematologic physiology, and also its impact specifically in the setting of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly Oxley et al noted an increased occurrence of younger SARS CoV2 virus-infected patients with no significant traditional risk factors for AIS, presenting with large vessel occlusion (6). Putative mechanisms suggested as inducing AIS in association with SARS CoV2 have included systemic inflammation, inflammatory cytokine storm, hyper-coagulability, and imbalances in the classical and alternative Renin Angiotensin System (RAS) in relation to SARS-CoV-2 spike glycoprotein-ACE2 binding related molecular mechanisms (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)). The RAS system comprises both a plasmabased RAS regulating cardiovascular system and tissue-based RAS regulating long term changes via a complex hormonal system, endocrine, paracrine, and autocrine in action.…”
Section: Introductionmentioning
confidence: 99%